Pembuatan Aplikasi 3 Dimensi Berbasis Augmented Reality pada Praktek Kerja Milling - Haris, Haris; Rahmat Hafiz; Malinda Hasian; Sicilia Afriyani (Fakultas Teknik UMRI, 2024)
The use of Augmented Reality (AR) technology in vocational education has grown rapidly, providing new opportunities to support practical learning processes. This research aims to develop an AR-based 3-dimensional application that is used in milling work practices, a basic technique in machining. This application is designed to help students understand fundamental concepts, operating procedures, and how to use milling machines in a more interactive and in-depth manner. Through this application, students can view 3D models of milling machines and their components, learn work steps through interactive simulations, and get visual guidance in a real AR environment. The development methods used include requirements analysis, system design, software development, and evaluation. The research results show that this application is effective in increasing students' understanding of milling material, as well as facilitating a more interesting and efficient learning process. It is hoped that the implementation of this application can become a model for the development of other educational technologies in the field of machining engineering.